Hydrotalcite Catalyst for Hydrocracking Calophyllum inophyllum Oil to Biofuel: A Comparative Study with and without Nickel Impregnation - Hafshah Hafshah; Danawati Hari Prajitno; Achmad Roesyadi (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
This research aims to study the effect of nickel impregnation into hydrotalcite catalyst that use to convert Calophyllum inophyllum oil into biofuel through hydrocracking process. Hydrocracking process was carried out under mild condition (350 °C and 20 bar) for two hours in a slurry batch reactor. The adding nickel affected the reaction conversion, yield, and selectivity of gasoil. The process of oxygen removal from the compounds in the oil was characterized by Fourier Transform Infrared Spectroscopy (FTIR), and the compositions of the products were determined by Gas Chromatography-Mass Spectrometry (GC-MS). The results of the study successfully proved that nickel impregnated into hydrotalcite catalyst increased the conversion, yield, and selectivity of gasoil up to 98.57 %, 54.15 %, and 81.31 %, respectively.